Urothelial Superior Vena Cava Syndrome with Limited Response to Radiation Therapy - Nishan Bingham; H. James Wallace III; Joanne Monterroso; Claire Verschraegen; Brenda L. Waters; Christopher J. Anker (Case Reports in Oncological Medicine)
Radiation therapy (RT) is the standard of care for cases of superior vena cava (SVC) syndrome secondary to metastatic adenopathy. Histologies vary in radiosensitivity and response time, making alternative therapies such as chemotherapy and/or intravenous stenting preferable alternative options for certain diagnoses. Metastatic urothelial carcinoma is a particularly rare cause of SVC syndrome with only 3 cases reported in the literature. Consequently, optimal management remains challenging, particularly in cases of high tumor burden. Here we present a case of highly advanced metastatic urothelial cancer with SVC syndrome and tracheal compression. The patient started urgent RT but expired midway through her treatment course due to systemic progression of disease, requiring SVC and tracheal stenting. The authors review the literature including discussion of the few other known cases of SVC syndrome due to urothelial carcinoma and a review of this histology’s response to RT. This experience suggests, that in cases of SVC syndrome with widespread advanced disease, stenting and chemotherapy with or without RT may be the most important initial treatment plan, depending on goals of care.